Analysis of Consumer Preference on Choosing E-Commerce in Indonesia - Lili Winda Sari; Achmad Manshur Ali Suyanto (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
For people who don't have much free time to shop, they can use e-commerce. because with e-commerce we can do it online, where shopping activities can be done without having to come directly to the store. The purpose of this study is to determine consumer preferences in choosing E-Commerce in Indonesia. The research method used is a quantitative method and data collection by questionnaire. The number of samples in this study was 451 people using the non-probability sampling method. The questionnaire items were 18 statements and the measuring instrument used was a Likert scale. The analysis technique in this study is conjoint analysis. The results of this study indicate that the highest utility value is at the transfer rate is 0.170, the attribute that has the highest importance value is the speed of the delivery attribute is 20,253, and consumers such as E-Commerce use the transfer payment method, shipping costs based on total weight product, 2-4 days delivery speed, has a product warranty that can be exchanged for the same product or product at the same price, website privacy security using a data security system, products sold according to the description given, and website appearance with a design interesting website.